MENGATASI DAN MENYIKAPI KESENJANGAN SOSIAL DENGAN MENGGUNAKAN PENERAPAN EKONOMI SYARIAH - Andini Septiani; Muhammad Iqbal Fasa; Suharto Suharto (Jurnal Bina Bangsa Ekonomika, 2022)
The economic sector is one of the important elements that support life, which in human daily life cannot be separated from the economy. However, various problems often arise because of the economic sector such as the problem of social inequality. This study aims to analyze socio-economic disparities, their causes, and solutions according to a review of the Islamic economic system. The research used is descriptive by using data and summarizing the results of previous research. The results show that it can be concluded that there are differences that include wealth, services, goods and others, resulting in the economic sector not working properly. Therefore, the application of Islamic economics is needed as a solution to overcome various problems due to the economic sector such as the problem of social inequality